(untitled) (Journal of Contemporary Studies, 2012)
Abstract Afghanistan presents a compelling case study in the discipline of international relations as over the past few centuries, the dynamics of major power rivalries, international systemic changes, geopolitics, energy politics, insurgencies and the phenomenon of terrorism have not only affected the Afghan society but also left its lasting imprints on regional and global security. This Research Paper explores the relevance of the structure of International system; identifies the stakes and interests of the key international, regional and local actors in the Afghan End-Game; evaluates the international system and its relationship with the interests and behaviour of these actors, both in the inter-regional and intra-regional contexts. In addition, a way forward is recommended to help achieve a viable Afghan state and a stable society along with defining a stabilizing role, which Pakistan can play in this respect for both itself, this region and towards promoting international security. The paper also identifies the opportunities and emerging challenges for local, regional and global players and compares their convergences and divergences of interests. Lastly, it also suggests ways of contributing towards the security and stability of both the Afghan nation and this volatile region, at a time when major and long-term shifts are underway in the 21st century political and security architecture of the world.